METHODS OF SUPERVISING LOCAL FINANCES. - Thomas, L. L. (The Accounting Review, 1944)
Abstract There is a great variation in the methods and extent of administrative supervision over local finance in the different states of the U.S. Each of the states exercises supervision to some extent. The purpose of this article is to examine the systems in use that are indicative of the better present-day conditions. It is planned to deal with only four phases of financial administration, namely, budgeting, accounting, auditing and reporting. It should be noted that there is a great variety in the name of the supervisory agency, in the appointment of the supervisory officer, in the term of office and in the salary. In most states the supervisory agency is in one of the already existing departments which is under the direction of either the State Auditor or the Comptroller. Since the agency is often in one of the department, the supervising officer is named after the department. The salary, the term of office and the method of selection all depend upon the state and upon whether the supervisory agency is a department in itself or is in connection with another department.